The Acoustic Self in English Modernism and Beyond Writing Musically - Varga, Zoltan (Taylor & Francis, 2022)
Drawing on the analogy between musical meaning-making and human subjectivity, this book develops the concept of the acoustic self, exploring the ways in which musical characterization and structure are related to issues of subject-representation in the modernist English novel. The volume is framed around three musical topics-the fugue, absolute music, and Gesamtkunstwerk-arguing that these three modes of musicalization address modernist dilemmas around selfhood and identity. Varga reflects on the manifestations of the acoustic self in examples from the works of E.M. Forster, Aldous Huxley, and Virginia Woolf, and such musicians as Bach, Beethoven, Handel, and Wagner. An additional chapter on jazz and electronic music supplements these inquiries, pursuing the acoustic self beyond modernism and thereby inciting further discussion and theorization of musical intermediality, as well as recent sonic practices. Probing the analogies in the complex interrelationship between music, representation, and language in fictional texts and the nature of human subjectivity, this book will appeal to students and scholars interested in the interface of language and music, in such areas as intermediality, multimodality, literary studies, critical theory, and modernist studies.